The Ten Differences Between Programs and Projects, and the Problems They Cause. Issue 2 (3rd April 2022) - Pollack, Julien; Anichenko, Ekaterina
Abstract: Program management has emerged as a growing area of research, supported by a range of popular normative guides. However, the line between programs and projects remains far from clear. This paper contributes to this field by identifying the ten cues that are typically used to distinguish programs from projects. Prototype theory is then introduced as a way of understanding the relationship between these two socially constructed categories. The paper argues that the structure of these categories leads to a tendency to extend from dominant images to less typical category members, with implications for practice.